Job satisfaction of utility workers at the university of the Philippines in the Visayas, Iloilo City campus - Gandarosa, Abdullah
This study dealt with the job satisfaction, work performance and work environment of utility workers in the University of the Philippines in the Visayas, Iloilo City Campus. The study implemented a descriptive method of research design, which described the nature and sources of job satisfaction, work performance and the effects on the work environment of the utility workers in UPV-CM, a survey was conducted by the researchers using a questionnaire. There were ten (10) randomly selected respondents in the study that came from the pool of utility workers at the city campus. The questionnaires that have been answered by the respondents were analyzed and interpreted using frequency distribution and were presented in tabular form. The results revealed that job satisfaction has no big effect on the work performance of the workers and the work environment that they are in the nature of the disatiifaction of the utility worker was contributed mainly of their relatively small salary and very few incentives. Even though that their salaries are small, they still learned to love their jobs.